Active nematics across scales from cytoskeleton organization to tissue morphogenesis - Balasubramaniam, Lakshmi; Mège, René Marc; Ladoux, Benoit (Current Opinion in Genetics & Development, 2022)
Biological tissues are composed of various cell types working cooperatively to perform their respective function within organs and the whole body. During development, embryogenesis followed by histogenesis relies on orchestrated division, death, differentiation and collective movements of cellular constituents. These cells are anchored to each other and/or the underlying substrate through adhesion complexes and they regulate force generation by active cytoskeleton remodelling. The resulting contractility related changes at the level of each single cell impact tissue architecture by triggering changes in cell shape, cell movement and remodelling of the surrounding environment. These out of equilibrium processes occur through the consumption of energy, allowing biological systems to be described by active matter physics. ‘Active nematics’ a subclass of active matter encompasses cytoskeleton filaments, bacterial and eukaryotic cells allowing them to be modelled as rod-like elements to which nematic liquid crystal theories can be applied. In this review, we will discuss the concept of active nematics to understand biological processes across subcellular and multicellular scales, from single cell organization to cell extrusion, collective cell movements, differentiation and morphogenesis.
CRIS-Team Scopus Importer:2024-02-19